Magnetic clusters in Co ion-implanted GaN - Kim, Woochul; Kang, Hee Jae; Noh, Sam Kyu; Song, Jonghan; Kim, Chul Sung (ELSEVIER, 2007)
The structural and optical properties of Co ion-implanted GaN were investigated by various measurements. HRXRD, TEM, and SADP results did not show any peaks associated with second phase formation. XPS depth measurements showed the metallic Co 2p core levels for 700-900 degrees C annealed-samples. From XPS results, it could be explained that magnetic property of our. lms originated from Co or CoGa magnetic clusters. The PL spectra obtained at 10K display a clear intensity modulation, indicating that the optical interference effect occurs in the layers. (C) 2006 Elsevier B.V. All rights reserved.